THE INFLUENCE OF CSR DISCLOSURE, ENVIRONMENTAL PERFORMANCE, AND INTERNAL CORPORATE GOVERNANCE ON THE ACHIEVEMENT OF SUSTAINABLE DEVELOPMENT GOALS - Agustin Aulia Farda; Erwin Saraswati (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2024)
Sustainable Development Goals (SDGs) require the involvement of various roles to support their achievement, especially from the business world. The research is aimed at examining the influence of CSR disclosure, environmental performance and Internal Corporate Governance on achieving the SDGs. The sample selected was 99 basic industrial and chemical companies listed on the Indonesia Stock Exchange (BEI) in the 2018-2022 period using the purposive sampling method. Data analysis uses unbalanced panel data regression analysis with the Eviews 12 application. The results of this research show that CSR disclosure in quantity and quality, environmental performance, and CEO non-duality, which are indicators of Internal Corporate Governance, have a significant effect on achieving the SDGs. On the other hand, other indicators of Internal Corporate Governance, namely board independence and board presence and the control variables of this research, namely size and leverage, do not have a significant effect on achieving the SDGs. Even though there is an influence between CSR disclosure, environmental performance and Internal Corporate Governance on the achievement of the SDGs, there are several factors that cause the influence of Internal Corporate Governance to not be maximized